2023
DOI: 10.21203/rs.3.rs-2751848/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between the expression of PSMB2 and proliferation and invasion in glioma

Abstract: There has been an upward trend in the incidence of glioma, with high recurrence and high mortality. The beta subunits of the 20S proteasome are encoded by the proteasome beta (PSMB) genes and may affect the proteasome's function in glioma, assembly and inhibitor binding. This study attempted to reveal the function of the proliferation and invasion of glioma cells, which is affectedby proteasome 20S subunit beta 2 (PSMB2). We subjected the data downloaded from the TCGA database to ROC, survival, and enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Its levels are significantly increased in various cancers, including HCC. In addition, PSMB2 is a member of proteasome 20S core beta subunit, which plays several roles in many types of cancers, such as gastric cancer [17] or glioma [18]. Previous studies have reported that PSMB2 was regulated by NUDT21.…”
Section: Discussionmentioning
confidence: 99%
“…Its levels are significantly increased in various cancers, including HCC. In addition, PSMB2 is a member of proteasome 20S core beta subunit, which plays several roles in many types of cancers, such as gastric cancer [17] or glioma [18]. Previous studies have reported that PSMB2 was regulated by NUDT21.…”
Section: Discussionmentioning
confidence: 99%